PENENTUAN MASAK FISIOLOGIS DAN PELAPISAN LILIN SEBAGAI UPAYA MENGHAMBAT KERUSAKAN BUAH SALAK KULTIVAR GADING SELAMA PENYIMPANAN PADA SUHU RUANG - Budi Santosa; Fauzia Hulopi (Universitas Tribhuwana Tunggadewi, 2008)
The research aimed to determine the appropriate harvest age of Salak Gading fruit to get the best quality and the longest storage period as well as to find out the effect of wax coating to ward the storage period and the quality of Salak Gading fruit at room temperature. The fruit was obtained from salak plantation at Turi Yogyakarta area. The research was divided into two stages. The first stage was the determination of ripe physiology in which the fruit was harvested at 6, 7 and 8 months after pollination. Afterwards the physical and chemical natures of the fruit were observed. The second one was wax coating in which the coated Salak Gading fruit was harvested at 7 and 8 days after pollination. The wax concentration used was 10% then the observation on physical and chemical nature were undergone once in three days. The determination of the storage period was accomplished when Salak Gading fruit has reached the level of decaying by 25% during the storage period. The results indicated that the best quality was at the period of 7 months. The wax coating influencing the quality of Salak Gading fruit also could keep loss down resulted from bacteria and inhibited the reduction of sugar and tannin inside the fruit. The determination of the harvest age of Salak Gading fruit and the wax coating could reform the quality of Salak Gading fruit